Use of Parthenium hysterophorus with synthetic chelator for enhanced uptake of cadmium and lead from contaminated soils—a step toward better public health - Ejaz, Ujala; Khan, Shujaul Mulk; Aqeel, Muhammad; Khalid, Noreen; Sarfraz, Wajiha; Naeem, Nayab; Han, Heesup; Yu, Jongsik; Yue, Gong; Raposo, António (Frontiers in Public Health, 2022)
Parthenium hysterophorus L. is a vigorous plant species with cosmopolitan distribution. It can uptake considerable quantities of heavy metals from the soil and accrue these metals in its different tissue. The use of chelating agent i.e., Ethylenediaminetetraacetic acid (EDTA) can boost up metal uptake capacity. Pot experiment was performed to evaluate phytoextraction potential of P. hysterophorus for lead (Pb) and cadmium (Cd) with and without the aid of EDTA chelator. Shoot length, weight of root and shoot (both fresh and dry), leaves number, and chlorophyll contents of P. hysterophorus got reduced with an increase in metal uptake. The results revealed the highest concentration of Cd in shoot without and with EDTA was 283.6 and 300.1 mg kg−1, correspondingly. Increase in Pb concentration was also boosted up by the EDTA from its maximum concentration in shoot 4.30–9.56 mg kg−1. Generally, Pb and Cd concentrations were greater in shoots of P. hysterophorus than the roots regardless of EDTA in the treatments. EDTA also impacted positively the accumulation of essential ions K+, Na+, and Ca+2 in P. hysterophorus. The capacity of P. hysterophorus to accumulate Pb and Cd found to be increased with EDTA in the soil. Bringing metals level in the soil in accordance to the WHO standards can improve the ecosystem as well as public health.